Strategi Peningkatan Keamanan Ruang Udara Indonesia di Era Digital Dalam Perspektif Hukum - Periani, Aniek; Djatmiko, Agoes; Kusumawardana, Haris (Universitas Ekasakti, 2023)
Every country in the world cannot avoid the unstoppable development of technology in the digital era. As is the case in the security sector, especially in the air space area. The purpose of this writing is to provide a reference for the Indonesian government to improve the security of Indonesian air space in the digital era through legal regulations. The research method uses a positive legal approach, namely the method or method used to obtain the law that applies at a certain time and place. Obstacles arising from law enforcement in Indonesia in implementing security in Indonesian airspace are due to the incompatibility of existing legal regulations with technology developing in the current era. So it is appropriate to make efforts to update legal regulations to align with the development of aerospace technology.